Perancangan dan Implementasi Sistem Smart Regulator Berbasis Internet of Things untuk Deteksi Kebocoran Gas LPG - Laksono, Muhammad Yurizard; Febriawan, Dimas (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research focuses on the design, implementation, and evaluation of an Internet of Things (IoT)-based Smart Regulator system developed to detect LPG gas leakage and to perform automatic, real-time safety actions through integration with a smartphone. The proposed system employs the NodeMCU Wemos ESP8266 as the main control unit, which is responsible for processing sensor data and coordinating all system components. LPG gas leakage detection is carried out using an MQ-5 gas sensor, capable of measuring LPG concentration in parts per million (PPM). As part of the safety response mechanism, the system is equipped with several output devices, including a buzzer and LED indicators as warning signals, an exhaust fan to reduce gas accumulation within the enclosed space, as well as a motor servo and a solenoid valve that function to automatically control the gas flow. Based on experimental testing, the system has demonstrated stable and consistent performance in detecting LPG gas leakage. When the detected gas concentration is below 300 ppm, the system remains in a normal operating state without activating any warning devices. When the gas concentration ranges between 300 and 400 ppm, the buzzer and visual indicators are automatically activated as an early warning mechanism. Furthermore, when the gas concentration reaches between 500 and 1000 ppm, the exhaust fan and the regulator valve control mechanism are automatically engaged to reduce gas accumulation and minimize the risk of fire hazards.